2020
DOI: 10.1186/s40981-020-00330-x
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin for postherpetic itch: a case report

Abstract: Background: Postherpetic itch has not commonly received attention as a complication of herpes zoster because pain predominates over itch in most patients with herpes zoster. Most cases of postherpetic itch are mild; however, cases of severe postherpetic itch reducing quality of life are rare. Case presentation: A 52-year-old woman complained of severe itch in her left pinna and cheek 1 month after the first onset of herpes zoster at the same site. Owing to her scratching, she developed ulcers on her left pinna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Although we did not investigate PHP severity, Shimada et al reported a case report of painless severe PHP. [ 6 ] Lee et al reported that the severities of pruritus and pain were significantly correlated in a small number of patients (N = 38). [ 10 ] On the other hand, Ishikawa et al reported no correlation of the visual analog scale score with PHP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although we did not investigate PHP severity, Shimada et al reported a case report of painless severe PHP. [ 6 ] Lee et al reported that the severities of pruritus and pain were significantly correlated in a small number of patients (N = 38). [ 10 ] On the other hand, Ishikawa et al reported no correlation of the visual analog scale score with PHP.…”
Section: Discussionmentioning
confidence: 99%
“…Gabapentin and pregabalin are effective in patients with PHP or other types of neurogenic pruritus. [ 6 , 21 ] Gabapentin and pregabalin are used to treat neuropathic pain because they act on signal routes that deal with painful stimuli. They also act on signal routes that deal with pruritic stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors felt its benefit is comparable with radiofrequency or chemical neurolysis of sympathetic ganglion 14 . In another recent study, Shimada et al 15 reported successful use of pregabalin 25 mg daily with prompt relief from the severe itching that was not responding to antihistamines. Ishikawa et al 16 studied PHI in acute, subacute, and chronic stages using Pain Detect Questionnaire and an itch‐intensity score and tried to correlate with neuropathic pain and found that these two sequelae have different mechanisms, needing different therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%